Perception toward low-cost generic medicines and their usage among dental patients visiting community outreach programs in the peripheral areas of Bangalore South: An exploratory cross-sectional survey - Nigy Johnson; Y Shweta Somasundara; Padma K Bhat; Santhosh Kumar; M Nayana (Wolters Kluwer Medknow Publications, 2020)
Background: The burden and prevalence of oral diseases are higher in developing countries, especially among the poor and disadvantaged populations. These people may suffer from various dental and systemic illnesses. Hence, provision of reducing the out-of-pocket money by purchasing generic drugs might enable better oral and general health-care-seeking behavior. Objectives: The objective was to assess the perception toward low-cost generic medicines available through the Pradhana Manthri Bhartiya Janaushadhi Pariyojana and their usage among dental patients visiting community dental outreach programs conducted in the villages near a tertiary care dental teaching hospital, Bangalore South. Materials and Methods: An exploratory descriptive cross-sectional survey was carried out over a period of 3 months among 200 residents participating in the dental outreach programs in 15 villages of Bangalore South. Data were collected using a prevalidated closed-ended interviewer-administered questionnaire. Results: Most respondents (82.5%) were not aware of Prime Minister Jan Aushadhi Kendra (PMJAK) and only 17.5% knew about the nearest PMJAK. The majority (96.5%) were not aware of the availability of dental-related medicines in PMJAK and (95.5%) preferred to buy Jan Aushadhi drugs over branded medicine if the quality of generic and branded medicine is the same. Most respondents (98%) liked to have more awareness through mass media about PMJAKs/medicines. Conclusion: The results indicate that more awareness must be created, and strict laws implemented about the Jan Aushadhi scheme to save health cost expenditure; if the quality of generic and branded medicine is the same, most people are willing to use the medicines sold at PMJA Kendras.